Konsep Keserasian Al-Qur’an Dalam Tafsir Mafatihul Ghaib Karya Fakhruddin Ar-Razi: Perspektif Ilmu Munasabah - Muhammad Fatih (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2022)
Fakhruddin ar-Razi stated, people who observe the beauty of the arrangement and order of the verses in the letter al- Baqarah, will undoubtedly realize that the miracles of the Qur'an are not only in the aspect of eloquence of lafadz-lafadz and the nobleness of its content, but also in the aspect of composition and structure. order of the verses. With the scientific approach of munasabah al-Qur'an, ar-Razi proved the above facts for himself as he described in his monumental commentary, Tafsir al-Kabir or Tafsir Mafatih al-Ghaib. Based on the author's research, there are at least nine kinds of munasabah in Tafsir al-Kabir by ar-Razi. First, munasabah sentence with sentence in one verse. Second, munasabah closing the verse with the content of the verse. Third, munasabah between verses in one letter. Fourth, munasabah between several verses in one letter. Fifth, munasabah between the letter opener and the closing letter. Sixth, musasabah between the contents of the letter. Seventh, munasabah between the opener of the letter and the closing of the previous letter. Eighth, munasabah between opening letters. Ninth, thematic unity in one letter. This research is library research with a qualitative approach. The primary data comes from Tafsir al-Kabir by Fakhruddin ar-Razi, while the secondary data comes from ulumul Qur'an books, commentaries, journal articles and scientific studies that discuss directly or indirectly about the theme in question. After the information and data were collected, the authors validated and tabulated based on certain objectives and considerations, then analyzed using descriptive-analytical methods. After comparing and observing the data and the analysis process, this study resulted in the conclusions as stated above.